Formation of hydroxy-sulfates from pyrite in coastal acid sulfate soil environments in Malaysia - Shamshuddin, J.; Jamilah, I.; Ogunwale, J.A. (Taylor & Francis Group, 1995)
Pyrite in hydromorphic soils is oxidized when it is exposed to the atmosphere. The sulfide oxidation releases hydrogen (H+) ions and other ions into the aqueous solution, and subsequently hydroxy-sulfates are formed. A laboratory aging experiment was conducted using coastal sulfate-rich soils in Malaysia to identify and determine the nature and composition of the hydroxy-sulfates and to explain the mechanism of their formation. Powder X-ray diffraction (XRD) analysis showed that incubating the pyrite-bearing soils in the presence of added electrolyte (KC1 and NaCl) resulted in the formation of jarosite, natrojarosite, and/or alunite. Subsequent transmission electron microscopy-energy dispersive X-ray (TEM-EDAX) analysis showed that a hydroxy-sulfate crystal was composed mainly of hydrogen (H), oxygen (O), sodium (Na), aluminum (Al), sulfur (S), potassium (K), and iron (Fe) which was accounted for as jarosite, natrojarosite, and/or alunite by powder XRD. The small amount of fluorine (F), nickel (Ni), titanium (Ti), and manganese (Mn) occurring within the same hydroxy-sulfate crystal was presumably originated from pyrite. This result points to the formation of hydroxy-sulfates in acid sulfate soils via psuedomorphic replacement of pyrite; under an oxidizing environment.